Significado da evolução eletrocardiográfica na doença de Chagas - Christiano Goncalves de Araujo (2008)
The cardiomyopathy is the main complication of Chagas disease. The baseline electrocardiogram (EKG) can demonstrate a wide range of abnormalities, and it is able to provide valuable clinical information regarding diagnosis and prognosis of this disease. The aim of this paper is to describe the evolution of the electrocardiographic findings after a mean 6.8 year follow up (+- 1.3 years), and make a correlation between the abnormalities that developed during this period and the decrease of the left ventricle ejection fraction (LVEF) of 5 percent or more. Methods: The trial was longitudinal, with prospective data acquisition. We enrolled patients with and without Chagas disease, from 15 to 55 years old, that met the inclusion criteria and did not have any other significant systemic or cardiac disease. The initial total sample consisted of 220 patients 30 in the control group and 190 in the chagasic group, enrolled from 1998 to 1999. 13 deaths occurred, all of them among the chagasic group (7.1% of the chagasic group), and they were not considered for this analysis. The final sample size was 153 patients, with a follow-up rate of 25 / 30 (83%) in the control group and 128 / 177 (72%) in the group with positive serology for Chagas disease. Results: During the follow up, 21 patients (18.7%) in the chagasic group and none of the patients in the control group had a significant decrease in the LVEF of 5% or more (p = 0.024). Over the study time, prolongation of the QRS complex duration, QT and QTc intervals, and increasing prevalence of low voltage on extremity leads were observed in the chagasic group. Only the occurrence of any electrocardiographic change and the prolongation of QRS duration correlate with the decrease of the LVEF of 5% or more. An increase of 0.005 seconds in the QRS complex duration has a sensitivity of 77.8% and specificity of 62.2% to distinguish the patients with a significant decrease of the LVEF. Conclusion: This study describes the follow up of an out-patient sample of chagasic patients, highlighting the importance of the EKG for the clinical management of these patients. The prolongation of the QRS complex e the new onset of electrocardiographic changes can help recognize the patients with a significant decrease in the LVEF.